A two‐stage network with prior knowledge guidance for medullary thyroid carcinoma recognition in ultrasound images. Issue 4 (17th February 2022) - Pan, Lin; Cai, Yanjing; Lin, Ning; Yang, Linxin; Zheng, Shaohua; Huang, Liqin
Abstract: Purpose: Accurate recognition of medullary thyroid carcinoma (MTC) is of great importance in medical diagnosis, as MTC is rare but second‐most malignant thyroid cancers with a high case‐fatality ratio. 1 But there is a lower recognition rate on distinguishing MTC from other thyroid nodules in ultrasound images, even by experienced experts. This paper introduces the computer‐aided method to tackle the challenge of recognizing MTC from ultrasound images, including limited MTC samples, and ambiguities among MTC, benign nodules, and papillary thyroid carcinoma (PTC). Methods: The recognition of MTC based on large MTC samples of ultrasound images has never been explored, as only one existing work presented a relevant dataset with a limited 21 MTC samples. This study proposes a novel method for primarily differentiating MTC samples from benign nodules and PTC that is the most common thyroid cancer. Our method is a two‐stage schema with two important components including a cascaded coarse‐to‐fine segmentation network and a knowledge‐based classification network. The cascaded coarse‐to‐fine segmentation network incorporates two U‐Net++ networks for improving the segmentation results of thyroid nodules. Meanwhile, our knowledge‐based classification network extracts and fuses semantic features of solid tissues and calcification for better recognizing the segmented nodules from the ultrasound images. In our experiments, dice similarity coefficient (DSC), intersection over union (IoU), precision, recall, and Hausdorff distance (HD) are adopted for evaluating the segmentation results of thyroid nodules, and accuracy, precision, recall, and F1‐score are used for classification evaluation. Results: We present a well‐annotated dataset including samples of 248 MTC, 240 benign nodules, and 239 PTC. For thyroid nodule segmentation, our designed cascaded segmentation network attains values of 0.776 DSC, 0.689 IoU, 0.778 precision, and 0.821 recall, respectively. By incorporating prior knowledge, our method achieves a mean accuracy of 82.1% in classifying thyroid nodules of MTC, PTC, and benign ones. Especially, our method gains the higher performance in recognizing MTC with an accuracy of 86.8%, compared to nearly 70% diagnosis accuracy of experienced doctors. The experimental results on our Fujian Provincial Hospital dataset further validate the efficiency of our proposed method. Conclusions: Our proposed two‐stage method incorporates pipelines of thyroid nodules segmentation and classification of MTC, individually. Quantitative and qualitative results indicate that our proposed model achieves accurate segmentation of thyroid nodules. The results also validate that our learning‐based framework facilitates the recognition of MTC, which gains better classification accuracy than experienced doctors.